A strategic plan for the Commission on Audit Regional Office No.XI - Bajo, Tessa Mae T. (School of Management, University of the Philippines Mindanao, 2007)
The Commission on Audit Regional Office No. XI or COA RO XI is the representative of COA in the region and was established in accordance with a reorganization law which was promulgated by President Decree No. 898 dated March 3, 1976. It exercises supervision and control over the implementation of auditing rules and regulations in all agencies of the government within the region and upon delegation by the Commission Proper, exercise authority and control on regional personnel, planning, financial and legal matters. This strategic plan is prepared to guide the Regional Cluster Director for Administration, in coordination with the different Regional Cluster Directors, in the effective and efficient delivery of public service and in recommending action plans to the COA Central Office. The specific issue that this study wants to address is: What strategy should COA RO XI undertake for the next five years in order to effectively and efficiently serve the public? The framework for this study follows the Strategic Planning Model of Fred R. David as adapted by Prof. Miguel D. Soledad of the University of the Philippines Mindanao. The strategic proposals were generated after an analysis of the external and internal environment of the organization was done. The environmental analysis identifies the critical factors that affect the success of COA RO XI in delivering service. Based on the identified factors, strategic options were then generated. The Quantitative Strategic Planning Matrix tool was used to identify the strategies of choice which are: 1. Intensity e-NGAS roll-out to government agencies 2. Intensity trainings on fraud audits and IT developments. The first strategy is expected to achieve the goal of becoming a vibrant partner in nation-building through the successful roll-out and implementation of the electronic New Government Accounting System (e-NGAS) to at least 10% of the government agencies annually. The second strategy is I line with the Commission?s goal of becoming an organization of professionals with a culture of excellence. The focus of this strategy is in the enhancement and development of skills of auditors in the field of fraud audits and IT developments. The effective implementation of the strategies of choice will lead to the attainment of the performance indicators identified. The coordination and support of all key personnel in the regional office, as well as the Executives in the Central Office, will greatly help in the realization of the strategies.